An Amperometric Biological Toxic Hydrazine Sensor Based on Multiwalled Carbon Nanotubes and Iron Tetrasulfonated Phthalocyanine Composite Modified Electrode. Issue 6 (21st April 2015) - Devasenathipathy, Rajkumar; Palanisamy, Selvakumar; Chen, Shen‐Ming; Karuppiah, Chelladurai; Mani, Veerappan; Ramaraj, Sayee Kannan; Ajmal Ali, M.; Al‐Hemaid, Fahad M. A.
Abstract Hydrazines are well‐known for their diverse biological properties but especially for their toxicity. An amperometric hydrazine sensor was developed at multi‐walled carbon nanotubes (MWCNT) and iron tetrasulfonated phthalocyanine (FeTsPc) composite modified electrode for the first time. The TEM and UV‐Vis spectroscopy results revealed the successful formation of MWCNT/FeTsPc composite. Compared with the response of MWCNT and FeTsPc modified electrodes, the MWCNT/FeTsPc composite showed enhanced oxidation current response with lower overpotential for hydrazine. Under optimum conditions, the amperometric i–t response of hydrazine was linear in the concentration range from 100 nM L−1 to 3 μM L−1 with the detection limit of 7.6 nM L−1. The response time of hydrazine was found as 6 s with a high sensitivity of 7.615 μA/μM L−1 cm−2.